2023
DOI: 10.1021/acs.jafc.3c01005
|View full text |Cite
|
Sign up to set email alerts
|

Splicing Indoles and 4,5-Dihydro-1H-pyrazoline Structure Gave Birth to Novel Antiviral Agents: Design, Synthesis, and Mechanism Study

Abstract: The specific conation of our research is to invent a series of indole derivatives containing a 4,5-dihydro-1H-pyrazoline motif with effective antiviral activity. The anti-potato virus Y (PVY) activities of target compounds were systematically investigated. Most target compounds exhibited good PVY activities. Compound D40, which exhibited outstanding anti-PVY activities, was sieved using a three-dimensional quantitative structure–activity relationship. Based on the anti-PVY activity assessments, the curative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…We conducted the interaction studies using a Nano Temper Monolith NT.115 (Nano Temper, Munich, Germany) MST apparatus and labeled the target proteins using a Monolith NT RED-NHS second-generation labeling kit following the manufacturer's protocol. We prepared the small molecule compounds, performed the pre-experimental setup, and processed experimental data following the experimental method described by Wang et al 28 We performed ITC binding measurements using an isothermal titration calorimeter (ITC200 GE Healthcare, Boston, MA) at 25 °C in a Q-B buffer. Before the experiment, we cleaned the apparatus using the method outlined by Bai et al 29 We performed the experiment with 0.1 mM VPg protein and 1 mM candidate compound.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted the interaction studies using a Nano Temper Monolith NT.115 (Nano Temper, Munich, Germany) MST apparatus and labeled the target proteins using a Monolith NT RED-NHS second-generation labeling kit following the manufacturer's protocol. We prepared the small molecule compounds, performed the pre-experimental setup, and processed experimental data following the experimental method described by Wang et al 28 We performed ITC binding measurements using an isothermal titration calorimeter (ITC200 GE Healthcare, Boston, MA) at 25 °C in a Q-B buffer. Before the experiment, we cleaned the apparatus using the method outlined by Bai et al 29 We performed the experiment with 0.1 mM VPg protein and 1 mM candidate compound.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It helps hosts develop resistance by affecting the polymerization of viral proteins, thus inhibiting viral assembly and reducing pathogenicity. Therefore, we selected it as a positive control agent in this study. …”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that the binding site space for the pyrazole group in OXA could accommodate larger molecular fragments. As we know, the indole ring is a functional and versatile fragment that has been widely applied in drug and pesticide design. Some of representative compounds ( compound 15–31 containing the indole ring are shown in Figure S1. Here, to continue our research on OXA, an indole fragment was introduced into OXA to replace the pyrazole ring (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Chalcones have been reported to exhibit a wide range of pharmacological activities such as antimicrobial [10][11][12][13], anticancer [14][15][16], anti-inflammatory [17][18][19], antiviral [20], and antioxidant [21,22]. Furthermore, heterocyclic compounds each bearing a pyrazoline scaffold have been reported as antimicrobial [23][24][25], anticancer [26][27][28], anti-inflammatory [29][30][31], antiviral [32], and antioxidant [33].…”
Section: Introductionmentioning
confidence: 99%
“…matory [17][18][19], antiviral [20], and antioxidant [21,22]. Furthermore, heterocyclic compounds bearing pyrazoline scaffolds have been reported as antimicrobial [23][24][25], anticancer [26][27][28], anti-inflammatory [29][30][31], antiviral [32], and antioxidant [33].…”
Section: Introductionmentioning
confidence: 99%